Redefining Corporate Social Responsibility and its relation to Sustainable Development Objectives - Mayorga Salamanca, Paola Irene (Mercados y Negocios, 2022)
The objective of this investigation is to redefine Corporate Social Responsibility (CSR) and its relation to Sustainable Development Objectives (ODS) based on organizational performance and competitiveness. The importance of including in those items new dimensions that currently acquire the item of sustainability in organizations. The main conclusion is that Corporate Social Responsibility constitutes one of the global efforts to translate sustainable development into something concrete and measurable.